2021
DOI: 10.1111/febs.16061
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐2 mediates ribosomal RNA transcription by cleaving nucleolar histones

Abstract: Cell proliferation and survival require continuous ribosome biogenesis and protein synthesis. Genes encoding ribosomal RNA are physically located in a specialized substructure within the nucleus known as the nucleolus, which has a central role in the biogenesis of ribosomes. Matrix metalloproteinase‐2 was previously detected in the nucleus, however, its role there is elusive. Herein we report that matrix metalloproteinase‐2 resides within the nucleolus to regulate ribosomal RNA transcription. Matrix metallopro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…During cerebral ischemia, MMP-2 targets DNA repair proteins poly ADP ribose polymerase (PARP)-1, X-ray repair cross complementing protein-1, and 8-oxoguanine DNA glycosylase-1 and decreases their activity in rat cortical neurons during I/R injury [131]. Our group recently detected MMP-2 inside the nucleolus of osteosarcoma cell lines where it promotes ribosomal RNA transcription and cell proliferation via, at least in part, cleavage of the N-terminal tail of histone H3 [132]. MMP-9 is also reported to be localized to the nucleus and regulate gene expression through selective proteolysis of the histone H3 tail during osteoclastogenesis [133].…”
Section: Nucleus/nucleolusmentioning
confidence: 99%
“…During cerebral ischemia, MMP-2 targets DNA repair proteins poly ADP ribose polymerase (PARP)-1, X-ray repair cross complementing protein-1, and 8-oxoguanine DNA glycosylase-1 and decreases their activity in rat cortical neurons during I/R injury [131]. Our group recently detected MMP-2 inside the nucleolus of osteosarcoma cell lines where it promotes ribosomal RNA transcription and cell proliferation via, at least in part, cleavage of the N-terminal tail of histone H3 [132]. MMP-9 is also reported to be localized to the nucleus and regulate gene expression through selective proteolysis of the histone H3 tail during osteoclastogenesis [133].…”
Section: Nucleus/nucleolusmentioning
confidence: 99%
“…Similarly, tumstatin, which is a 28 kDa matrikine released by MMP9 from the α3-chain of type IV collagen (COL4α3), was found to suppress cancer growth through αvβ3 integrin-mediated antiangiogenic activity. It was observed that MMP9-deficient mice were characterized by decreased levels of circulating tumstatin linked to an increased rate of tumor growth, and this effect was reversed upon restoration of the physiological concentration of tumstatin in blood [ 154 ]. Additionally, MMP9 was reported to have a tumor suppressor role in colitis-associated cancers (CACs) by the activation of Notch1-dependent intracellular signal transmitters that triggered cell apoptosis, cell-cycle arrest, and DNA damage [ 155 , 156 ].…”
Section: Mmp9 and Cancermentioning
confidence: 99%
“…The localization of MMP-2 to the promotor region of the ribosomal DNA genes in the nucleolus suggests it regulates ribosomal RNA transcription [6]. Indeed inhibition of MMP-2 genetically or pharmacologically was associated with reduced both pre-ribosomal RNA transcription and cell proliferation [87]. We also found that nucleolar MMP-2 activity regulates RNA transcription through the clipping of histone H3, as H3 cleavage is associated with increased ribosomal RNA transcription and minimal or absence of H3 cleavage, when MMP-2 is inhibited, results in reduction in transcription, as well as cell proliferation [87].…”
Section: Novel Roles Of Mmp-2 Inside Cellsmentioning
confidence: 99%
“…Indeed inhibition of MMP-2 genetically or pharmacologically was associated with reduced both pre-ribosomal RNA transcription and cell proliferation [87]. We also found that nucleolar MMP-2 activity regulates RNA transcription through the clipping of histone H3, as H3 cleavage is associated with increased ribosomal RNA transcription and minimal or absence of H3 cleavage, when MMP-2 is inhibited, results in reduction in transcription, as well as cell proliferation [87]. Another study also found that MMP-9 (Gelatinase-B, closely related to MMP-2) is able to clip histone H3 and regulates genes expression involved in melanoma formation [88].…”
Section: Novel Roles Of Mmp-2 Inside Cellsmentioning
confidence: 99%